2015
DOI: 10.11648/j.sjph.20150305.40
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Characteristics of Patients Diagnosed with Osteogenesis Imperfecta at the Zambia Italian Orthopedics Hospital Community Based Rehabilitation Project

Abstract: Introduction: Osteogenesis Imperfecta is a rare condition that can be very disabling. It is an inherited disease of the bones, which is characterized by fragility that causes affected individuals to have recurrent fractures that subsequently lead to pain, deformity and disability. The aim of the study was to determine the prevalence of Osteogenesis Imperfecta and identify the common deformities and treatment methods used in managing affected individuals at the Zambia Italian Orthopedics Hospital. Methods: This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…The mean age of the present study was 6.96 years. A study from Kabengo et al found that most of the patients diagnosed with OI were under 10 years old [21]. Type III OI was the most common type in this study.…”
Section: During Thesupporting
confidence: 52%
See 1 more Smart Citation
“…The mean age of the present study was 6.96 years. A study from Kabengo et al found that most of the patients diagnosed with OI were under 10 years old [21]. Type III OI was the most common type in this study.…”
Section: During Thesupporting
confidence: 52%
“…Similarly, Newacheck stated that there was no difference in gender preference in children with OI [20]. In contrast, Kabengo et al found that female prevalence was more profound than male [21]. The mean age of the present study was 6.96 years.…”
Section: During Thecontrasting
confidence: 43%
“…In the past year, the mean number of fractures was 2.50 (SD 6.51) times, with the femur being the most common fracture site in 17 children with OI [21].…”
Section: Discussionmentioning
confidence: 99%